Antiinflammatory, antinociceptive and antipyretic effects of hydroethanolic extract from Macrosiphonia velame (A. St.-Hil.) M. Arg. in animal models - Reginaldo Vicente Ribeiro; Regilane Matos da Silva; Joaquim Corsino da Silva Lima; Domingos Tabajara de Oliveira Martins (Universidade de São Paulo, 2010)
Macrosiphonia velame (Apocynaceae), popularly known as "velame-branco", is mainly used for treating inflammatory conditions. The antiinflammatory, antinociceptive and antipyretic effects of the hydroethanolic extract of the xylopodium from M. velame (HEMv) were evaluated using several animal models. HEMv showed low acute oral toxicity with LD50 of 4.176 ± 218.5 mg/kg in mice. In tests of carrageenan and dextran-induced paw edema and carrageenan-induced pleurisy in rats, and croton oil-induced cutaneous dermatitis in mice, HEMv presented systemic and topical antiinflammatory activities. In experiments of nociception induced by acetic acid, formalin and capsaicin in mice, the HEMv evidenced an antinociceptive effect, being active against both inflammatory and neurogenic pain. Additionally, the HEMv prevented brewer's yeast-induced pyrexia in rats. It is likely that the pharmacologic mechanism of HEMv may involve the inhibition of different mediators of the inflammatory response, such as histamine, serotonin, prostaglandins and leukotrienes. A preliminary phytochemical study was also undertaken on HEMv, which revealed the presence of flavonoids, phenolic compounds, pentacyclic triterpenoids, saponins, coumarins, catechins, tannins, and alkaloids. Taken together, these results suggest that M. velame extract has antiinflammatory, antinociceptive and antipyretic properties and further validate the traditional use of this plant in inflammatory conditions. Macrosiphonia velame (Apocynaceae), conhecida popularmente como velame-branco, é utilizada no tratamento de inflamações. Avaliou-se nesse estudo, os efeitos antiinflamatório, antinociceptivo e antipirético do extrato hidroetanólico do xilopódio de M. velame (HEMv) em modelos animais. O HEMv apresentou baixa toxicidade aguda oral, com DL50= 4.176 ± 218,5 mg/kg nos camundongos. Nos testes de edema de pata por carragenina e dextrana e pleurisia por carragenina em ratos e dermatite cutânea por óleo de croton em camundongos, o HEMv apresentou atividade antiinflamatória sistêmica e tópica. Nos experimentos de nocicepção induzida por ácido acético, formalina e capsaicina em camundongos, o HEMv inibiu a resposta nociceptiva nos três modelos, mostrando-se ativo tanto na dor de origem inflamatória como neurogênica. Adicionalmente, o HEMv bloqueou a hipertermia induzida por levedura de cerveja nos ratos. É provável que os efeitos farmacológicos observados para o HEMv decorram da inibição de mediadores da resposta inflamatória produzidos pelas vias da COX e/ou LOX bem como da inibição da liberação de histamina e serotonina. A análise fitoquímica do HEMv revelou a presença de flavonóides, compostos fenólicos, triterpenóides pentacíclicos, saponinas, cumarinas, catequinas, taninos catéquicos e alcalóides. Estes resultados validam sob o ponto de vista pré-clínico, o uso popular de M. velame em processos inflamatórios.